Comparative study of the bone graft area and fusion rate in unilateral transforaminal lumbar interbody fusion between Endoscopic and Miniopen procedures. A technical note and preliminary report - Kang Taek Lim; Hyung-Suk Kim; Elmer Jose Arevalo Meceda; Han Gawi Nam; Chun-Kun Park (International Journal of Spine Research - Peertechz Publications, 2020)
Spinal fusion surgery can now be performed through the endoscopic approach. Adequate endplate preparation and sufficient contact between bone graft or bone graft substitutes with the surfaces of the vertebral endplates are main factors to achieve successful arthrodesis. The purpose of this study are to compare the bone graft area, ratio of allograft-bonegraft (allo-bone) to total disc area, fusion rate, functional and radiographic outcomes between Endoscopic and Mini-open TLIF and to introduce the endoscopic technique of endplate preparation and implantation. Methods: Hospital records of 59 patients who underwent TLIF (Endoscopic fusion, 23; Mini-open TLIF, 36) for the period of January 2017 to June 2018, were reviewed. Immediate postoperative CT scans were used to measure the bone graft area of an index segment by getting a mid-disc level slice on CT. The bone graft area and the ratio of the area occupied by allo-bone against the total disc area were computed. Perioperative outcomes such as operation time, length of hospital stay, and incidence of surgical complications were also recorded and analyzed. The Visual Analog Scale (VAS) were assessed 1week, 1month, and 12 months after surgery. Oswestry Disability Index (ODI) were evaluated preoperative, and 12months after surgery in both groups. The restoration of disc height (DH), segmental lumbar lordosis (SLL), fusion rate were also reviewed at 12months postoperatively. The endoscopic technique of endplate preparation and implantation were described in detail. Results: The bone graft area ratio were significantly higher in endoscopic group (42.4±20.3%) than in the Mini-open group (32.3±2.8%), (p<0.01) in immediate postoperative CT scan. The VAS were significant lower in endoscopic TLIF at postoperative 1week than Mini-open TLIF (p < 0.05), and both were identically improved at 12months with no significant difference between the two groups as was the ODI. DH, SLL were significantly increased in both group at 12 months (p<0.01). Fusion rate for both procedures were considered to be satisfactory at 12months postoperatively, but there was not significantly different between the two groups (Endoscopic TLIF, 95.6%, Mini-open TLIF, 94.4%, p= 0.977). Conclusion: The bone graft area and area ratio were significantly higher in Endoscopic group than Mini-open TLIF. Both techniques however, provided excellent clinical results with low complication rates. More effective instruments should be developed for Endoscopic TLIF to reduce the operation time.